Green Mussels (Perna viridis L.) Culture in Mangrove Area Potentially Impacted by Heavy Metal - Suyono Suyono; Rossita Shapawi; Narto Narto (Marine Science Department Diponegoro University, 2019)
The purposes of this study are to investigate the types of different collectors and their most effective height of installation in the green mussels cultivation (Perna viridis L.) impacted by heavy metal pollution in mangrove and non-mangrove waters; and to determine the content of heavy metals, especially Pb, Cu, Cd, and Hg in green mussels cultivation. This research was conducted from April to September 2018 in the coastal area of Karangdempel, Losari Sub District, Brebes Regency. The method used in this research was experimental. The results showed that the growth of green mussels after 6 months period of maintenance reached 7-9 cm long, weighing 10-13 grams per head and yielded 23-30 heads per collector. The most effective mussel collector was net sacks installed at a height of 30 cm from the bottom of the water. The number of mussels per collector was more in mangrove location compared to those in the non-mangrove location, while their growth in length and weight were relatively the same. Heavy metal content in seawater and in the mussel meat are still within the permissible limits of the Indonesian National Standard, except for the Cu content in the mussel exceeding the allowable limit; but it was relatively still safe accoring to the Decree of the Director General of Drug Control and Food, Indonesian Ministry of Health, No. 03725/B/SK/1989. Pb content in sediments in both location of green mussels cultivation and the Cisanggarung River basin is still within the safe limits. The content of Cd, Cu, and Hg in sediments tends to be high. Heavy metal content both in mangrove and non-mangrove areas was not different as a result of mangrove reforestation dominated by seedlings and saplings with little influence on the quality of the water ecologically and economically.